Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae) - Beccacece, Hernán Mario; Zapata, Adriana Inés (Zootaxa, 2017)
Arctiini (Lepidoptera, Erebidae, Arctiinae) is the most speciose tribe of tiger moths. In this study, the taxonomy of some Neotropical species of this tribe is reviewed based on habitus and, in some cases, genitalia of type specimens. Lectotypes are designated for two names. Four new combinations are proposed: Agaraea sericeum (Zerny, 1931) comb. n., Biturix nigrostriata (Rothschild, 1909) comb. n., Carales fasciatus (Rothschild, 1909) comb. n. and Opharus pallida (Dognin, 1910) comb. n. Six new synonymies are proposed: Agaraea nigrotuberculata Bryk, 1953 (=Agaraea klagesi (Rothschild, 1909)), Opharus ochracea Joicey & Talbot, 1918 and Pelochyta fergusoni Watson & Goodger, 1986 (=Opharus pallida (Dognin, 1910)), Melese flavescens Joicey & Talbot, 1918 (=Melese paranensis Dognin, 1911), Leucanopsis infucata (Berg, 1882) (=Pareuchaetes aurata aurata (Butler, 1875)) and Tessellota pura Breyer, 1957 (=Tessellota cancellata (Burmeister, 1878)). Moreover, Opharus ochracea Joicey & Talbot, 1918 comb. rev. is returned to the original genus. For each rearrangement, both remarks and information about type specimens are provided.